Медичні (психіатричні) аспекти виправлення неповнолітніх осіб, засуджених до покарання у виді позбавлення волі - Карпінська, Н.; Осадовський, Т.; Karpinska, N.; Osadovskyi, T. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті здійснено аналіз національного законодавства та міжнародних стандартів у сфері медичного забезпечення в установах виконання покарань, результатів судово-психіатричних експертиз неповнолітніх. Автор обгрунтував необхідність функціонування спеціальних установ виконання покарань для осіб із психічними аномаліями, що буде важливим стимулом для проведення комплексного дослідження зв’язків, що обумовлюють злочинну поведінку таких осіб, їх мотиваційної сфери. Головна мета діяльності такого роду спеціальних установ з виконання покарання має полягати, в першу чергу, в наданні необхідної психіатричної допомоги та застосуванні диференційованих медичних та виправних заходів. Потребує вирішення проблема запровадження на державному рівні статистичної звітності стану, структури та динаміки злочинності осіб із психічними аномаліями, в тому числі неповнолітніх.The article is devoted to the analysis of the forensic psychiatric examinations results of juveniles, national laws and international standards in the sphere of medical provision in prisons. According to the World Health Organization, 1.2 million of Ukrainians suffer from mental illnesses. For many years number of mental disorders of Ukrainians occupies the first place in Europe. The author justifies the creation of a special hospital for the application of compulsory medical measures for juveniles. The object of the article is legal analysis of the state of medical (psychiatric) provision of sentenced to imprisonment juveniles in the light of their rehabilitation. The author emphasizes that despite the fact that peculiarities of providing medical (psychiatric) care to juveniles are conditioned by clinical specificity of mental disorders and a number of international normative acts and national legislation, there is no system of child forensic psychiatry in Ukraine. The author makes conclusions that there is a need to put into practice a state-level statistical reporting as to the status, structure and dynamics of crime of the individuals with mental aberrations, including juveniles. He examines a possibility of creating an independent special hospital for psychiatric help for convicred juveniles and indicates the need to harmonize national legislation with international standards in the field of health (psychiatric) provision for convicts.
Medical (Ppsychiatric) Aspects of Rehabilitation of Juveniles Sentenced to Imprisonment
Keywords: психічні аномалії; судово-психіатрична експертиза; неповнолітні особи; установи виконання покарань; примусові заходи медичного характеру; mental aberrations; forensic psychiatric examination; juveniles; penal institutions; forced medical measures